2012
DOI: 10.4049/jimmunol.1201964
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus (CMV)-Induced Memory-like NKG2C+ NK Cells Are Transplantable and Expand In Vivo in Response to Recipient CMV Antigen

Abstract: We have previously shown that NKG2C+ NK cells from CMV naïve umbilical cord blood (UCB) grafts expand preferentially in recipients after CMV reactivation, representing a primary NK cell response after hematopoietic cell transplantation (HCT). In this study, recipients of adult donor HCT were assessed to evaluate the role of donor/recipient CMV serostatus on the expression and function of NKG2C+ NK cells in order to determine responses to secondary CMV events. Expansion of NKG2C+ NK cells was seen following cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
326
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(342 citation statements)
references
References 31 publications
16
326
0
Order By: Relevance
“…Subsequent studies of patients who were infected by HCMV or in whom the virus was reactivated owing to immunosuppression after solid organ or haematop oietic stem cell transplantation confirmed that the CD94-NKG2C + NK cell population preferentially expands during acute HCMV infection, subsequently persist as memory cells and can constitute up to 70% of the total NK cell population in some individuals [34][35][36] . Moreover, after haematopoietic stem cell transplantation, CD94-NKG2C + NK cells from HCMV-seropositive donors demonstrated enhanced function in response to re-exposure to HCMV in HCMV-seropositive recipients whereas CD94-NKG2C + NK cells from HCMVseronegative donors did not, suggesting the existence of a memory response against HCMV infection 37 . In in vitro experiments in which HCMV-infected fibroblasts were co-cultured with NK cells either knocked down for HLA-E by short hairpin RNA or treated with CD94-or NKG2C-specific blocking antibodies 38 , the interaction of CD94-NKG2C with its ligand HLA-E 39 was shown to drive the expansion of the CD94-NKG2C + NK cell population (FIG.…”
Section: Box 1 | Memory In Myeloid Cells In Mammalsmentioning
confidence: 96%
“…Subsequent studies of patients who were infected by HCMV or in whom the virus was reactivated owing to immunosuppression after solid organ or haematop oietic stem cell transplantation confirmed that the CD94-NKG2C + NK cell population preferentially expands during acute HCMV infection, subsequently persist as memory cells and can constitute up to 70% of the total NK cell population in some individuals [34][35][36] . Moreover, after haematopoietic stem cell transplantation, CD94-NKG2C + NK cells from HCMV-seropositive donors demonstrated enhanced function in response to re-exposure to HCMV in HCMV-seropositive recipients whereas CD94-NKG2C + NK cells from HCMVseronegative donors did not, suggesting the existence of a memory response against HCMV infection 37 . In in vitro experiments in which HCMV-infected fibroblasts were co-cultured with NK cells either knocked down for HLA-E by short hairpin RNA or treated with CD94-or NKG2C-specific blocking antibodies 38 , the interaction of CD94-NKG2C with its ligand HLA-E 39 was shown to drive the expansion of the CD94-NKG2C + NK cell population (FIG.…”
Section: Box 1 | Memory In Myeloid Cells In Mammalsmentioning
confidence: 96%
“…CMV also skews the NK cell receptor repertoire in humans, with cells expressing the activating heterodimer NKG2C/CD94 expanding in recipients of solid organ74 or umbilical cord blood (UCB) transplantation75 during primary CMV infection or reactivation. These cells have an enhanced ability to secrete IFN γ in response to target cells or, even more so, upon CMV reactivation 74, 75, 76. Therefore, it has been suggested that these cells represent the human counterparts of Ly49H+ NK cells with memory‐like properties.…”
Section: Subsets Of Nk Cellsmentioning
confidence: 99%
“…NK cells acquire a mature phenotype CD56+ (CD56 dim ) during CMV activation (178). In solid organ transplant patients, acute CMV infection increases the CD57+ NKGDC hi (memory phenotype) pool, which appears to be CMV specific (179).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%
“…In early stages of CMV infection, CMV binding of TLR2 and the CD14 cofactor on monocytes trigger inflammatory cytokine production via activation of NF-kB (173 NK cell activation in the early host responses to CMV manifests with IFN-c production, direct cytotoxicity and ADCC (178). NK cells acquire a mature phenotype CD56+ (CD56 dim ) during CMV activation (178).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%